Pendekatan Cooperative Learning Tipe STAD: Peningkatkan Keterampilan Membuat Bantal Karakter Pada Anak Tunagrahita Ringan - Saputri, Popi; Irdamurni (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
This research is based on the problems that researchers found in the class X/C tunagrahita ringan in SLB N 1 Pariaman in October 2019. Learning skill of making character pillow in children with tunagrahita ringan, the ability of children in practicing activities to make character pillow is still not good and not correct, and have not estabilished a good cooperation in the process of making. The purpose of this research are to prove whether cooperative learning approach of STAD type can improve the skill of making character pillow in tunagrahita ringan children, and describe the learning process in improving the skill of making batako through cooperative learning approach STAD class X at SLB N 1 Pariaman.The type of research used is classroom action research, conducted in the form of collaboration with classroom teachers. As a research subjects were three children with tunagrahita ringan grade X/C and one classroom teacher. The result obtained through observation, and tests deeds. Then analyzed with qualitatively and quantitatively methods. The results of research after being given tratment for eight times showed that the initial ability before the treatment of making by DW 43%,YD 34%, LT 31% and SR 41%.While at the end of the cycle I the ability of DW increased (49%), YD (37%),LT (35%) and SR (45%).In cycle II the ability of DW increased to (87%), YD (74%) , LT (72%) and SR (86%).